Water Partnership Program : Strategic Action Plan 2012-2016 - World Bank (Washington, DC, 2014)
Water is a fundamental platform for economic and social development, and contributes to reducing multiple dimensions of poverty. It is essential to food and energy security, industrial growth, and the protection of ecosystems. Water has been going through unprecedented pressures as growing populations and economies have increased demand and at the same degraded supplies. As a result, water insecurity has become one of the greatest risks facing the world today. The WPP's strategic action plan describes the program's vision and strategic directions for its second phase, running from July 2012 to June 2016. It explains the rationale for scaling-up activities and provides details of the structural changes under second phase. The objectives, impacts, and expected outcomes of second phase are outlined in the next section. In addition, the strategic action plan includes plans to scale up partnership efforts, communications and knowledge management. Finally, it presents a new results framework to measure the impact of second phase.